Active home surveillance system (COD19) in managing chronic obstructive pulmonary disease: lessons and future perspectives from the COVID-19 pandemic experience - Andrea Foppiani; Valeria Calcaterra; Chiara Montanari; Simona Bertoli; Alberto Battezzati; Gianvincenzo Zuccotti (Therapeutic Advances in Respiratory Disease)
Background: During the COVID-19 pandemic, telemedicine became crucial for monitoring chronic conditions, including respiratory diseases. Objectives: This study, part of a larger cohort of COVID-positive patients, focuses on individuals with chronic obstructive pulmonary disease (COPD) monitored through an active home surveillance system (COD19). Design: Longitudinal telematic active surveillance study. Methods: The study included COVID-19-positive patients in home isolation, quarantined workers, and those discharged from ASST hospitals or emergency departments. At discharge, patients received a letter with isolation guidelines, a COD19 kit (oxygen meter, thermometer, protective devices), and instructions for monitoring clinical parameters. Regular phone check-ins by physicians were conducted, starting within 12 h of activation. A secure platform COD19 enabled data collection and communication between patients, healthcare providers, and regional authorities. Results: The study involved 1288 patients, including 226 (17.5%) with COPD, who were older ( p  < 0.001), had a higher BMI ( p  = 0.006), and were more frequently admitted from home isolation ( p  < 0.001). COPD patients also had higher mean body temperature ( p  = 0.011) and respiratory rate ( p  = 0.035), with a non-significant trend toward lower SpO 2 values. Monitoring outcomes indicated that COPD patients were more likely to require higher levels of care ( p  < 0.001), and the only two deceased patients were from this group. The remote monitoring service received positive feedback, with a median answering ratio of 92%, reflecting strong patient participation and manageable monitoring processes. Conclusion: The findings underscore telemedicine’s effectiveness in COPD management, ensuring continuity of care and smooth home-to-hospital transitions. The system enhanced accessibility, enabling consistent monitoring and timely interventions. As healthcare evolves, telemedicine remains a key tool in improving patient care and accessibility.